The Notion of Relevance in Academic Collaboration: From Setting Objectives to Targeting Development Goals - Tamrat, Wondwosen (International Journal of African Higher Education, 2022)
This article examines the notion of relevance in academic collaboration between North and South partners. It traces the history and nature of academic cooperation, and the major factors that determine the success of partnerships. It is argued that equitable, collaborative agenda setting, clear decision-making procedures, and consideration of the developmental goals that are the envisaged outcome of collaboration schemes are mechanisms that can be used to address issues of relevance. Failure to address relevance concerns could result in academics or institutions being diverted from addressing local or national priority areas. In turn, this could result in the relevance of the cooperation itself being questioned.